Pengembangan Perangkat Pembelajaran Model Brain Based Learning Materi Barisan dan Deret untuk meningkatkan Kemampuan Pemecahan Masalah - Nuranita Adiasstuty (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2015)
ABSTRACT The research aims to develop a learning devices on Brain Based Learning (BBL), to enhance the problem solving abilities. This research is a development by using models Plomp, which consists of the initial investigation phase, design phase, construction phase of realization or phase test, evaluation, and revision, and implementation phase. The study was conducted in vocational Islamic Centre Cirebon on three sample classes. Variables include the study of learning, motivation, skills, processes, teacher and student response, and problem solving skills. Data collection techniques (in a row) using validation sheets, tests, questionnaires, observation, and TKPM sheet. The results showed the average value of the syllabus, lesson plans, student books, LKS row in the range of 1-5 is 4.55; 4.32, 4.45 and 4.40 so that the study considered valid. Positive response shown by the students and teachers towards learning, which indicate the practical learning. Increase problem solving ability. motivation and skills of the students, the effect of 81.5% of the students' problem-solving abilities. The average of the results of the test problem solving skills 77.56 KKM exceed 70, so that the average problem-solving ability to learn to use Brain Based Learning is better than average ability to use problem solving methods ekspository. It is concluded that the study is valid, practical, and effective. Keywords: effective, Brain Based Learning, problem solving abilities